Search for the rare decay Λ+c→pμ+μ− - Aaij R. Roel; Adeva B. Bernardo; Adinolfi M. Marco; Aidala C. Christine; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen